A Bioecological View of Culturally Sustaining Pedagogy - Billen, Rhett M.; Billen, Monica (Educational (Re)naissance, 2022)
Culturally sustaining pedagogy (CSP) considers the impacts of schools on communities, explicitly calling upon schools to sustain instead of overlook the cultural modalities of communities of color (Paris, 2012). In this paper, we argue that one important influence schools should have on families is the awareness and knowledge that families’ culture are sustained and viewed as “official knowledge” (Ladson-Billings, 1995) in the education system. We do so by including a perspective found in the disciplines of developmental science, family science, and education, Bronfenbrenner’s bioecological theory. Specifically, we examine the principles of CSP from the Person-Process-Context-Time (PPCT) model within bioecological theory. Furthermore, we problematize the traditional practice of assigning homework and offer an implication for reimagining homework from a CSP lens. Keywords: culturally sustaining pedagogy, bioecological theory, homework, family storytelling, PPCT model